Peningkatan Pengetahuan dan Ketrampilan dalam Bidang Bahasa dan Budaya di Desa Kare Kabupaten Madiun - Akhmad Jayadi; Prihartini Widiyanti; Gadis Meinar Sari; Fitriyatul Qulub (I-Com: Indonesian Community Journal, 2023)
Kare Village is one of the villages in Madiun Regency which has a variety of tourism potential, both natural and cultural. However, this tourism potential has not been utilized optimally. Ecotourism is carried out with a focus on increasing the active role of local communities. In the Assisted Village Development Program (PPDB) activities, seminars on local cultural potential identity and cultural preservation, English language training and draw pattern in piece of clothes (batik) making training were conducted for PKK women and Kare Village batik craftsmen. Community service with the topic of ecotourism aims to develop tourist village areas on the basis of participation and cooperation, increase understanding of tourism village marketing and realize sustainable tourism. This activity consists of three stages, namely preparation, implementation of activities, and follow-up activities. In its implementation, the community service program for the Assisted Village Development Program (PPDB) has held workshops with the theme of exploring local wisdom, applied tourism English language training with the aim of supporting sustainable ecotourism in Kare Village and batik batik training. This community service aims to make Kare Village ecotourism better and capable of international standards and can improve the welfare of the Kare Village community.